BIPHASIC ASYNCHRONOUS GENERATOR WITH CONDENSER EXCITATION - Berzan V.P.; Tirshu M.; Birladean A. (Problems of the Regional Energetics)
In article two-winding asynchronous generator in biphasic execution with the capacitor excitation, executed on the basis of the asynchronous engine with a short-circuited rotor is considered. Researches of the developed generator are executed under various schemes of connection of stator windings. Selecting phases wire numbers of stator windings implemented for various voltages with inclusion on a phase of the raised voltage of excitation condensers, allowed decreasing the size of capacity and improving indicators and generator characteristics.